Sport and mental health performance optimization in an adolescent gymnast: A case evaluation - Phrathep, Davy; Donohue, Brad; Renn, Brenna N.; Mercer, John; Allen, Daniel N. (Frontiers in Sports and Active Living, 2023)
The Optimum Performance Program in Sports (TOPPS) is a multi-component, sport-specific Family Behavior Therapy that has demonstrated improved sport performance, relationships, and mental health outcomes in adult and adolescent athletes with, and without, diagnosed mental health disorders in clinical trials. The current case trial demonstrates successful implementation of a novel component of TOPPS (i.e., talk aloud optimal sport performance imagery leading to dream mapping) in a biracial Latina and White adolescent gymnast without a mental health diagnosis. The participant demonstrated significant improvements from baseline to both post-treatment and 3-month follow-up in severity of mental health functioning, factors interfering with sports performance, and her relationships with teammates, coaches, and family. Results suggest it may be possible to optimize mental health through sport performance optimization.